From Media Literacy to New Media Literacy: Adapting to the Changing Conditions - Devrim Eserol, Nehir (Journal of Computer and Education Research, 2025)
The concept of media literacy has developed into a sophisticated and dynamic field which attracts researchers from social science disciplines including communication and education. Multiple scholars have tried to define media literacy, but their definitions show both disciplinary viewpoints and changing communication requirements. The emergence of new media and multimodal communication requires a redefinition of current media literacy frameworks. This research conducts a systematic review of media literacy and new media literacy research to identify major similarities and differences and emerging trends through qualitative analysis of academic studies. The article examines the educational aspects of social media through multiple academic disciplines. Social media literacy requires immediate attention, yet experts disagree about the essential principles needed to develop educational programs. The main difference between traditional media literacy and new media literacy lies in their focus on content analysis versus user-generated content creation. The research provides a fresh understanding of social media literacy by identifying both commonalities and distinctions between media literacy and social media literacy.